Menguak Sanksi Nyongkok dalam Penyelesaian Kredit Macet Ditinjau dari Perspektif Nasabah, Pengurus LPD dan Hukum Adat (Studi Kasus Pada LPD Desa Pakraman Telaga, Kecamatan Busungbiu, Kabupaten Buleleng) - Putri, WP Kartika; Atmadja, Anantawikrama Tungga (Universitas Pendidikan Ganesha, 2020)
This study aims to find out: (1) how is the background of applying nyongkok customary sanction to the LPD at Desa Pakraman Telaga, (2)what are the types of nyongkok customary sanction that are applied, and (3) how are the implications of applying nyongkok customary sanction in the settlement of bad debts on LPD at Desa Pakraman Telaga. This research was conducted at the LPD at Desa Pakraman Telaga, Busungbiu District, Buleleng Regency. This study uses a qualitative methods. The data used in this study are primary data and secondary data. The results of this study stated that (1) the background that applying nyongkok customary sanction is to bind customers to remember the responsibility to repay all loans along with interest as well as being a strength for the sustainability of the LPD at Desa Pakraman Telaga and to provide a detterent effect for customers, (2) the type of nyongkok customary sanction is not getting served in the village in religious ceremonies except death and all the obligation proceed as usual, and (3) the implications that arises from the application of nyongkok customary sanctions is the existence of awig-awig is maintained to regulate society, the exixtence of LPD at Desa Pakraman Telaga as a support for the village economy, fear arises not having the ability to repay loans, and there was the emergence of shame when announced as a nyongkok sanction customer durng a meeting with the community.Â Â